Estudio de factibilidad para la producción y comercialización de helados de carao en la ciudad de Guayaquil. - Cornejo Salcedo, Nicolle Dennisse (2019)
The next venture involves the development and marketing of Carao Ice Cream and other exotic fruits, offering them under an existing novel concept. In the first chapter of this project, we focused on a brief investigation about the fruit, we defined the theoretical framework orienting ourselves in theories of entrepreneurship, feasibility study, micro-enterprises, and financing to micro-enterprises. In the same way, in this chapter, we defined the techniques of the research process using the technique of observation and surveys, which our sample showed a value of 384 respondents. In the second chapter, we pointed out the PESTAL analysis where it helped us to have a more specific idea of the scenario we were going to face. In the same way, we analyzed PORTER, where we determined what the positive and negative influence for the business was. An analysis of the supply and demand of the ice cream industry was also determined. In the third chapter of the project, we defined the strategic planning of the company, the administrative management, and at the same time all the costs and the investment that we need. We made a statistical model (Incident Inference) where we demonstrated the acceptance of the alternative hypothesis of our project. For chapter four, we identified our business model and to whom and how we will focus on the market for the supply of our products. Finally, in the fifth chapter, the viability of the business was shown to be profitable using financial indicators such as NPV ($448.080,61) as income with a TIR of 54.21% and a PAY BACK to recover the investment approximately in 16 months of implementation the business is running.